2021
DOI: 10.1007/s10823-021-09432-0
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge and Attitudes of two Latino Groups about Alzheimer Disease: a Qualitative Study

Abstract: Clustering Latinos under a single group in Alzheimer Disease (AD) research, neglects, among other things cultural and environmental differences. To address this, we examine knowledge and attitudes about AD among two Latino groups. We held 5 focus groups and 2 interviews all in Spanish with Mexicans and Puerto Ricans between 40 and 60 years old living in the Grand Rapids area in Michigan. Using content analysis of the discussions, we identified themes related to knowledge, attitudes and concerns about AD and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, for Spanish-speaking populations served by LAC-DHS, part of this education may also require directly addressing cultural beliefs around dementia and equipping caregivers with tools to educate other family members. Our focus groups identified that many of the historically negative views of dementia, and equating a dementia diagnosis with being “crazy”, can limit family support and may even limit a family’s acceptance of the diagnosis [ 9 , 10 , 11 , 12 , 26 ]. As this cultural view of dementia is a fundamental step in accepting dementia as a pathologic disease, we recommend early exploration and education on cultural beliefs of dementia for Hispanic dyads at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, for Spanish-speaking populations served by LAC-DHS, part of this education may also require directly addressing cultural beliefs around dementia and equipping caregivers with tools to educate other family members. Our focus groups identified that many of the historically negative views of dementia, and equating a dementia diagnosis with being “crazy”, can limit family support and may even limit a family’s acceptance of the diagnosis [ 9 , 10 , 11 , 12 , 26 ]. As this cultural view of dementia is a fundamental step in accepting dementia as a pathologic disease, we recommend early exploration and education on cultural beliefs of dementia for Hispanic dyads at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study, involving five focus groups and two interviews in Spanish with participants aged 40 to 60 in Michigan, revealed common themes like improving knowledge and awareness, barriers, and home-based family care. Puerto Rican participants expressed more concerns about the disease, while Mexicans highlighted a lack of knowledge as a significant theme [ 35 ]. While Latino individuals are often categorized based on linguistic similarities, this term encompasses a highly diverse group in terms of geography, culture, race, and genetics [ 36 ].…”
Section: Influences Of Hispanic Culturementioning
confidence: 99%
“…For instance, some people may search for detailed information on a topic, whereas others may seek brief or no information at all (Ford et al, 2002; Friis et al, 2003; Leydon et al, 2000). In Latino communities, stigma can be associated with the diagnosis of Alzheimer’s disease or related dementias, receiving mental health services, and placing aging parents in assisted living facilities (Beyene et al, 2002; Cabrera et al, 2021; Fripp & Carlson, 2017; Martinez & Acosta Gonzalez, 2022). This can influence the amount of information Latinos seek about these topics.…”
mentioning
confidence: 99%